ANALISIS EFEKTIVITAS PENERIMAAN PAJAK REKLAME DALAM MENINGKATKAN PENDAPATAN ASLI DAERAH KABUPATEN SIDOARJO TAHUN 2021-2025 - Mutia Viayuvada; Aliza Putri Amelia; Muhammad Ady Nursetya; Talitha Rifqi Risqulloh; Oktavia Kurnia Ramadhani; Fatma Anriyani Yusuf; Melda Fadiyah Hidayat; Revienda Anita Fitrie (Jurnal Aplikasi Perpajakan, 2026)
This study aims to determine the effectiveness of advertisement tax revenue and to examine its contribution to increasing Regional Original Revenue (PAD) in Sidoarjo Regency from 2021 to 2025. This research employs a descriptive method with a quantitative approach, utilizing secondary data obtained from regional financial reports (LKPJ). The analytical techniques used include effectiveness analysis and contribution analysis of tax revenue to PAD. The results of this study indicate that advertisement tax revenue during the 2021–2025 period falls into the very effective category, as evidenced by the realization of tax revenue consistently exceeding the predetermined targets. In nominal terms, tax revenue has increased annually, reflecting the growing potential of the advertisement sector as well as improved performance in tax management by the local government. However, the contribution of advertisement tax to PAD remains relatively low, with a percentage of less than 1% of the total PAD. Overall, both advertisement tax revenue and PAD in Sidoarjo demonstrate effective performance with a positive growth trend. Therefore, continuous optimization is required through improved data collection and supervision, as well as the utilization of digital systems to maximize the potential of advertisement tax revenue in the future.